Long-Term Use of Proton Pump Inhibitors Disrupts Intestinal Tight Junction Barrier and Exaggerates Experimental Colitis. (2nd November 2022) - Nighot, Meghali; Liao, Pei-Luan; Morris, Nathan; McCarthy, Dennis; Dharmaprakash, Viszwapriya; Ullah Khan, Inam; Dalessio, Shannon; Saha, Kushal; Ganapathy, Ashwinkumar Subramaniam; Wang, Alexandra; Ding, Wei; Yochum, Gregory; et al.
Abstract: Background: Proton pump inhibitors [PPIs] are widely used to treat a number of gastro-oesophageal disorders. PPI-induced elevation in intragastric pH may alter gastrointestinal physiology. The tight junctions [TJs] residing at the apical intercellular contacts act as a paracellular barrier. TJ barrier dysfunction is an important pathogenic factor in inflammatory bowel disease [IBD]. Recent studies suggest that PPIs may promote disease flares in IBD patients. The role of PPIs in intestinal permeability is not clear. Aim: The aim of the present study was to study the effect of PPIs on the intestinal TJ barrier function. Methods: Human intestinal epithelial cell culture and organoid models and mouse IBD models of dextran sodium sulphate [DSS] and spontaneous enterocolitis in IL-10 −/− mice were used to study the role of PPIs in intestinal permeability. Results: PPIs increased TJ barrier permeability via an increase in a principal TJ regulator, myosin light chain kinase [MLCK] activity and expression, in a p38 MAPK-dependent manner. The PPI-induced increase in extracellular pH caused MLCK activation via p38 MAPK. Long-term PPI administration in mice exaggerated the increase in intestinal TJ permeability and disease severity in two independent models of DSS colitis and IL-10 −/− enterocolitis. The TJ barrier disruption by PPIs was prevented in MLCK −/− mice. Human database studies revealed increased hospitalizations associated with PPI use in IBD patients. Conclusions: Our results suggest that long-term use of PPIs increases intestinal TJ permeability and exaggerates experimental colitis via an increase in MLCK expression and activity.